2012
DOI: 10.1117/12.926484
|View full text |Cite
|
Sign up to set email alerts
|

Design, analysis, and testing of the optical tube assemblies for the ESO VLT four laser guide star facility

Abstract: TNO has developed the Optical Tube Assemblies (OTAs) for the ESO VLT Four Laser Guide Star Facility. The OTAs are Galilean 20x beam expanders, expanding a ∅15 mm input beam (25W, 589 nm CW) to a steerable ∅300 mm output beam. TNO has recently successfully completed acceptance testing of the four units, showing compliance to the challenging requirements on output wavefront quality, thermally induced defocus under operational conditions, absolute pointing accuracy and polarization extinction ratio (PER).TNO appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The laser, BCDS and OTA are mounted on a steel baseplate, which is aligned in tilt with respect to the UT4 optical axis during integration. The OTAs have been manufactured by TNO in Delft, Netherlands, adopting the ESO reference optical design [58]. The beam expanders of the BCDS were manufactured by Optec S.r.l (Parabiago, Italy).…”
Section: Laser Guide Star Unit: System Description and Overviewmentioning
confidence: 99%
“…The laser, BCDS and OTA are mounted on a steel baseplate, which is aligned in tilt with respect to the UT4 optical axis during integration. The OTAs have been manufactured by TNO in Delft, Netherlands, adopting the ESO reference optical design [58]. The beam expanders of the BCDS were manufactured by Optec S.r.l (Parabiago, Italy).…”
Section: Laser Guide Star Unit: System Description and Overviewmentioning
confidence: 99%
“…In space, the relative pose (positions and orientations) of the optical elements, especially between the primary lens and the rear lens group, will change due to the changes in the thermal environment and the structure, which will seriously affect the imaging quality of the telescope [ 9 , 10 , 11 ]. Furthermore, it is found that the tilt and decentration of the primary lens will make the telescope imaging quality decrease obviously [ 12 , 13 ]. Therefore, the pose measurement of the telescope primary lens has become difficult to overcome urgently in membrane optical imaging technology [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…ESO is also procuring a launch telescope as part of the VLT adaptive optics facility 18 currently being manufactured by TNO 19 in the Netherlands.…”
Section: Laser Launch Subunitsmentioning
confidence: 99%